THE EFFECT OF PEPPERMINT AROMATHERAPY ON THE INTENSITY OF NAUSEA AND VOMITING IN PREGNANT WOMEN IN THE FIRST TRIMESTER I - Heni Frilasari (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
A woman experiences pregnancy, which lasts from conception (fertilization) until the baby is born. Excessive nausea and vomiting, or hyperemesis gravidarum, can also negatively impact the developing fetus, including abortion, low birth weight, premature delivery, and birth defects. This study aims to determine the effect of peppermint aromatherapy on the intensity of nausea and vomiting in patients with hyperemesis gravidarum. The research design used in this study is Pre Experimental Designs. The population in this study were all Hyperemesis Gravidarum Patients at TPM Ny. Fifin Nur Indah for 1 month totaling 25 while the sample in this study was Hyperemesis Gravidarum Patients totaling 25 using Non-probability Sampling with Total sampling method. The measuring tool or instrument in this study was The Rhodes Index Nausea Vomiting and Retching (INVR). This analysis was to find the relationship between the independent variable and the dependent variable using cross tabulating and the Wilcoxon statistical test with a significance level of 0,05. Before the intervention, most of the respondents experienced hyperemesis gravidarum with nausea and vomiting in the moderate category, as many as 22 respondents (88%). After the intervention, most of the respondents experienced hyperemesis gravidarum with nausea and vomiting in the mild category, as many as 20 respondents (80%). There was a decrease in nausea and vomiting in 80% of respondents. Based on the results of the Wilcoxon test, the probability value Asym.sig 2 P-Value 0.000 failed <0.05, so H1 is accepted, meaning there is an effect of Peppermint Aromatherapy on the intensity of nausea and vomiting in Hyperemesis Gravidarum patients. With complementary therapy, Peppermint Aromatherapy provides good benefits for pregnant women with nausea and vomiting and is certainly safe for pregnant women because it uses herbs.